1997
DOI: 10.1128/aac.41.3.583
|View full text |Cite
|
Sign up to set email alerts
|

In vivo efficacy of trovafloxacin (CP-99,217), a new quinolone, in experimental intra-abdominal abscesses caused by Bacteroides fragilis and Escherichia coli

Abstract: The efficacy of trovafloxacin in treating Bacteroides fragilis and Escherichia coli infections was investigated and compared to the efficacy of combined clindamycin and gentamicin therapy in an experimental model of intra-abdominal abscesses in rats. Rats were treated with different doses of CP-116,517-27, a parenteral prodrug of trovafloxacin. Response to treatment was evaluated by mortality rate and elimination of infection (cure rate). Mortality in the control group was 85.4%, whereas in rats treated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…This lack of correlation between survival and elimination of bacterial burden suggests that trovafloxacin, too, exerts an effect on cytokines in this infection model. In rats injected with heat-killed B. fragilis and E. coli, trovafloxacin partially reduced the serum concentrations of TNF-α [62]. These data suggest that trovafloxacin modulates the production and/or secretion of TNF-α , thus, contributing to its in vivo efficacy against mixed infections in rats.…”
Section: In Vivo Studies -Intra-abdominal Infectionsmentioning
confidence: 85%
See 1 more Smart Citation
“…This lack of correlation between survival and elimination of bacterial burden suggests that trovafloxacin, too, exerts an effect on cytokines in this infection model. In rats injected with heat-killed B. fragilis and E. coli, trovafloxacin partially reduced the serum concentrations of TNF-α [62]. These data suggest that trovafloxacin modulates the production and/or secretion of TNF-α , thus, contributing to its in vivo efficacy against mixed infections in rats.…”
Section: In Vivo Studies -Intra-abdominal Infectionsmentioning
confidence: 85%
“…The decrease in mortality rate and elimination of infection was dose proportional. In general, TNF-α levels were low in all trovafloxacin-treated animals [62,63]. The protective effect of trovafloxacin could probably be due to its antibacterial efficacy, as trovafloxacin exerts a significant in vitro activity against both anaerobes as well as Enterobacteriaceae [64].…”
Section: In Vivo Studies -Intra-abdominal Infectionsmentioning
confidence: 94%
“…Onderdonk [38], using a mixed cecal inoculum, and Thadepalli et al [39], using a combination of B. fragilis and E. coli, found comparable efficacy of trovafloxacin with that of clindamycin and gentamicin in the therapy of an experimental intra-abdominal abscess model. Stearne et al [40] compared the efficacy of trovafloxacin in a murine subcutaneous model of mixed infection with B. fragilis and E. coli or B. fragilis and vancomycin-resistant Enterococcus faecium (VREF).…”
Section: Trovafloxacinmentioning
confidence: 95%
“…In similar experiments, Stearne et al [8] found that trovafloxacin was able to decrease abscess weight as well as the bacterial counts of B. fragilis (MIC, 0.25 mg/mL) after treatment for 5 days. In experimental intraabdominal abscesses caused by B. fragilis (MIC, 0.24 mg/mL) and E. coli, trovafloxacin as a single agent was observed to produce survival rates that were comparable to those resulting from treatment with clindamycin plus gentamicin [7]. Onderdonk [87] also studied the effectiveness of trovafloxacin in a rat model of intra-abdominal sepsis.…”
Section: Pharmacodynamicsmentioning
confidence: 96%
“…Ciprofloxacin lacked in vitro potency against many important anaerobic bacteria, but several newer quinolones looked promising [2][3][4][5][6]. Trovafloxacin was the first fluoroquinolone to receive approval from the US Food and Drug Administration for the treatment of anaerobic bacteria, such as Bacteroides fragilis, Peptostreptococcus species, and Prevotella species isolated from patients with intra-abdominal and pelvic infections [7,8]. Levofloxacin and sparfloxacin are not as potent as trovafloxacin in vitro but possess good activity against selective anaerobic bacteria [9,10].…”
mentioning
confidence: 99%